Valuing changes in the portfolio of service flows from climate-induced extremes on a linked food, energy, water system (C-FEWS) - Chang, Joseph W.; Ando, Amy W.; Chen, Mengye (Frontiers in Environmental Science, 2023)
Recent work examining the impact of climate-change induced extremes on food-energy-water systems (FEWS) estimates the potential changes in physical flows of various FEWS parameters. However, it is also important for decision makers to consider the potential changes in monetary value attributed to the observed changes in physical flows from these events. We develop a valuation tool (FEWSVT) that applies theoretically sound valuation techniques to estimates changes in value for four parameters within the food-energy-water nexus. We demonstrate the utility of the tool through the application of a case study that analyzes the monetary changes in value of a modelled heat wave scenario relative to historic (baseline) conditions in two study regions in the United States. We find that food (corn and soybeans) comprises the majority (89%) of total changes in value, as heatwaves trigger physical changes in corn and soybeans yields. We also find that specifying overly simplified and incorrect valuation methods lead to monetary values that largely differ from FEWSVT results that use accepted valuation methods. These findings demonstrate the value in considering changes in monetary value when making decisions on how to distribute investments and address the many potential impacts of climate change-induced extremes.